À la recherche des points-clefs de Gilbert Simondon autour d’un système d’information géographique - Stephan Kowal (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The main topic of this article is the development of the Canada Geographic Information System (CGIS) initiated in 1962, an integrated computer system capable of combining national statistical information and cartographic documents, specifically intended for decision-making in regional planning. The text revisits the political and economic context leading to the development of the first system of this type, arising from the Canada Land Inventory (CLI), a government program stemming from the Agricultural Rehabilitation and Development Act (ARDA), which was expanded to include all rural development. It is the cartographic nature of this system developed in Canada, and the transfer of hand-drawn cartographic documents into a digital format through the binary system, which provides renewed insights into important changes concerning conventional representation theory. Through close examination of these automatic and non-automatic transcription devices developed in the 1960s, and more precisely, through the development of a device specifically designed for this system, the Special Cartographic Scanner, this text deals with the transition from hand-drawn maps to manipulable digital databases. This article examines the nature of cartographic information in terms of point, line, surface, scale and frame, disrupting certain conventions of representation and drawing, through digitising procedures, as well as a new technique of sequencing files, the introduction of the world’s coordinate system, regions of processable data, and their overlay. It demonstrates that notions of position, line and frame in conventional representation have changed for the benefit of a digital point and selection. In an effort to link digital cartography to architectural design, this article exemplifies the transition from representations based on the human eye, developed since the Renaissance, to the use of remote sensing devices and computer-generated imageries, pattern recognition, influencing decision-making and design, with the system’s capacity to generate new knowledge with the overlay and combination processes of point elements. It situates the Canada Geographic Information System within the context of Cybernetics and Information theories, and in turn positions it within philosopher Gilbert Simondon’s theory of concretization of technical objects and of his key points theory, linking technical objects to the territory, considered as subjective and aesthetic productions.